Three‐Dimensional Structural Analysis of MgO‐Supported Osmium Clusters by Electron Microscopy with Single‐Atom Sensitivity1. Issue 20 (16th April 2013) - Aydin, Ceren; Kulkarni, Apoorva; Chi, Miaofang; Browning, Nigel D.; Gates, Bruce C.
<x xml:space="preserve">Abstract</x> Size, shape, nuclearity: Aberration‐corrected scanning transmission electron microscopy was used to determine the 3D structures of MgO‐supported Os3, Os4, Os5, and Os10 clusters, which have structures nearly matching those of osmium carbonyl compounds with known crystal structures. The samples are among the best‐defined supported catalysts.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>